POTENCY OF ZEOLITE IN INDONESIA - Kusdarto, Kusdarto (Jurnal Zeolit Indonesia, 2008)
Zeolite is one of non-metallic minerals or multi-use industrial minerals due to its physical and chemical characteristic as an absorbent, ion exchange, molecular filters and as a catalyst. Minerals in zeolite group are generally found in tufa rocks formed from volcanic-ash sediments resulting from alteration, diagenesis, and hydrothermal processes. Indonesia is laid in the volcanic series from Sumatra, Java, Nusa Tenggara, until Sulawesi Islands. One of the products of volcanic tuff wide spreading form the volcano, partially or wholly have undergone a process of alteration or diagenesis to become zeolite. Geologically, Indonesia has big potential to produce zeolites such as those found in Lampung, West Java, Central Java, East Java, East Nusa Tenggara, and Sulawesi, with the estimate resources of 447,490,160 tons.